Technique For Teaching Announcement TextAt The Seventh Grade Of SMP Negeri 1 Sambi In 2016/2017 Academic Year - Yusuf, Muhammad Wildan, Drs. Djoko Srijono.,M.Hum (2016)
This research aims at describing the technique for teaching announcement text at the seventh grade of SMP Negeri 1 Sambi in 2016/2017 academic year. The objectives of the research are to describe the technique for teaching announcement text at the seventh grade of SMP Negeri 1 Sambi in 2016/2017 academic year and to describe the advantages and disadvantages of technique for teaching announcement text faced by the teacher at the seventh grade of SMP Negeri 1 Sambi in 2016/2017 academic year. This research is a descriptive study. The subject of the research focuses on English teacher and the seventh grade students of seventh grade of SMP Negeri 1 Sambi. In collecting the data, the researcher uses observation, document analysis, and interview. The collected data are analyzed by collecting, reducing, and displaying data, classifying and verifying the data, and drawing conclussion. Based on the research finding, it was found the techniques for teaching announcement text are explanation, reading, questioning, discussion, and controlled writing. It was always done by the teacher in every teaching activity. The advantages of techniques are: 1) Explaining, the teacher feels comfortable to deliver the material. 2) Reading, the teacher more relaxed because the teacher does not deliver the material too much. 3) Discussion, the teacher can find out who the students are active or not and also know how character for each students. 4) Questioning, the teacher can find out who already understand or not from the material has been delivered. 5) Controlled writing, the teacher can train students to be more careful and know with the content. The disadvantages of the techniques are: 1) Explanation. It can take a lot of time, teacher can be tired, and many students behave negatively. 2) Reading. It takes time. 3) Discussion. The teacher feels difficult to manage students, some students not focus and makes joke with the members of his group. 4) Questioning. It takes time because some students answer the wrong answer and he should correct it first before giving a wrong answer more questions to other students. 5) Controlled writing. The teacher will spend a lot of time because the teacher is preoccupied with too many students who do not understand the tenses used and should guide them to understand. Keywords: teaching technique, teaching announcement text